Processo de busca e recuperação de informação em ambientes organizacionais: Uma reflexão teórica sobre a subjetividade da informação - Valentim, Marta Lígia Pomim [UNESP]; Teixeira, Thiciane Mary Carvalho (FapUNIFESP (SciELO), 2017)
The efficient retrieval of information relevant for organizational business still constitutes a challenge for information managers, especially if the goal is stimulate and facilitate wide access to information generated internally and externally to the organization, aiming to carry out strategic actions. From this perspective, information management has become a crucial activity for organizations, in other words, information scanning and mining that facilitate strategic decisions and actions, in order to provide organizational competitive advantages. The conditions of access and seeks for the appropriation and use of information in organizational contexts has become a complex activity due to the subjectivity of information, this characteristic requires that the manager of information to develop a keen insight regarding the informational world, so that meet the informational needs and demands effectively.
Process of search and retrieval of information in organizational environments: A theoretical reflection on the subjectivity of information
Keywords: Information access; Information appropriation; Information retrieval; Information seeking; Information use; Organizational environment